ECONOMIC BENEFITS OF LEFT VENTRICULAR HYPERTROPHY REGRESSION IN PATIENTS WITH ARTERIAL HYPERTENSION - E. I. Tarlovskaya; N. S. Maksimchuk; S. V. Malchicova; M. V. Avksentieva; I. E. Sapozhnikova; Y. A. Balandina (Столичная издательская компания, 2016)
Aim. To evaluate by modelling the economic benefits of left ventricular hypertrophy (LVH) regression in patients with arterial hypertension (HT) due to therapy with fixed combination of valsartan/amlodipine.  Material and methods. 20 patients (15 females and 5 males, aged 18 to 70 years) with essential HT accompanied by metabolic syndrome with a history of previous ineffective antihypertensive therapy were included into the study. All patients were treated with fixed combination of amlodipine/valsartan in doses of 5/160 and 10/160 mg depending on blood pressure (BP) level. Treatment duration was 24 weeks. Changes in BP level, LVH regression were assessed. Economic evaluation was performed on the basis of modelling with the specialized software Decision Tree 4.xla. Results. Effect of fixed amlodipine/valsartan combination therapy on LVH was used to estimate treatment effectiveness and to build the model. Patients were distributed according to left ventricular (LV) mass (at baseline and after 24 weeks of therapy). Significant decrease in LV mass from 205.8±50.4 to 181.9±45.1 g (p<0.05) was revealed. The model took into account economic and frequency factors for 10 year prognosis: this therapy prevents 36 deaths, 6 strokes, 24 myocardial infarction per 1000 patients. Absence of need in treatment of these prevented events can save 2 516 772.42 RUR for every 1 000 patients. It would reduce the total costs per patient during 10 years. Conclusion. Treatment with amlodipine/valsartan single pill combination has not only clinical advantages, but also pharmacoeconomic benefits. This combination reduces risk of acute myocardial infarction and death more effectively. Treatment with fixed valsartan/amlodipine combination saves maximum years of life with less cost during 10 years. Despite of higher pharmacotherapy costs, fixed valsartan/amlodipine combination reduces total costs due to prevention of fatal and nonfatal cardiovascular events.